2c(7c+5)=0

Simple and best practice solution for 2c(7c+5)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2c(7c+5)=0 equation:


Simplifying
2c(7c + 5) = 0

Reorder the terms:
2c(5 + 7c) = 0
(5 * 2c + 7c * 2c) = 0
(10c + 14c2) = 0

Solving
10c + 14c2 = 0

Solving for variable 'c'.

Factor out the Greatest Common Factor (GCF), '2c'.
2c(5 + 7c) = 0

Ignore the factor 2.

Subproblem 1

Set the factor 'c' equal to zero and attempt to solve: Simplifying c = 0 Solving c = 0 Move all terms containing c to the left, all other terms to the right. Simplifying c = 0

Subproblem 2

Set the factor '(5 + 7c)' equal to zero and attempt to solve: Simplifying 5 + 7c = 0 Solving 5 + 7c = 0 Move all terms containing c to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 7c = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 7c = 0 + -5 7c = 0 + -5 Combine like terms: 0 + -5 = -5 7c = -5 Divide each side by '7'. c = -0.7142857143 Simplifying c = -0.7142857143

Solution

c = {0, -0.7142857143}

See similar equations:

| A^2-3ab-28b^2=0 | | -3a+9=3a | | 65=.2(w-40) | | (w+9)(w-15)=0 | | 13xy+18xy-20xy= | | 65=.2(w-10)4 | | 1+5y=8x-20 | | 4x+6x-17=2(2x+3x) | | -y+124=30 | | 9a+2=20 | | -t*42=3 | | 4a+12=4 | | -10m-8m=-24 | | 14/1+6/3 | | 1/2(6m-10)=3m-5 | | 27b+12b= | | 35=.2(255-10e) | | 3x+6=27+3 | | -1.1428x-6=-2.6x-14 | | (x+1)(x-1)(x-3)(x-6)=0 | | 6=-9-6 | | 51-7x=12+(-4x) | | 2x+3+5x=13 | | 5+3(n+9)=-3 | | 5+x-3[x+4]=-17 | | f(x)=2x+x-1 | | 3n-13=n+6 | | (x+5)(x-5)(x-7)=0 | | x^2+8x-7=8 | | 16x+18y+10x-7y= | | 5y^2+8y= | | 3k-2=39 |

Equations solver categories